Intramuscular Fat Infiltration Evaluated by Magnetic Resonance Imaging Predicts the Extensibility of the Supraspinatus Muscle - Giambini, Hugo (Muscle Nerve, 2017)
INTRODUCTION: Rotator cuff (RC) tears result in muscle atrophy and fat infiltration within the RC muscles. An estimation of muscle quality and deformation, or extensibility, is useful in selecting the most appropriate surgical procedure. We determined if non-invasive quantitative assessment of intramuscular fat using MRI could be used to predict extensibility of the supraspinatus (SSP) muscle. METHODS: Seventeen cadaveric shoulders were imaged to assess intramuscular fat infiltration. Extensibility and histological evaluations were then performed. RESULTS: Quantitative fat infiltration positively correlated with histological findings and presented a positive correlation with muscle extensibility (r = 0.69; p = 0.002). Extensibility was not significantly different between shoulders graded with a higher fat content vs. those with low fat when implementing qualitative methods. DISCUSSION: A non-invasive prediction of whole-muscle extensibility may directly guide pre-operative planning to determine if the torn edge could efficiently cover the original footprint while aiding in postoperative evaluation of RC repair.